Oxicopis cerdai, una nueva especie chilena de Oedemiridae (Coleoptera: Tenebrionoidea) - Ramirez F, F.
(Es, En)
Ilus., 19 ref.
Keywords: COLEOPTERA; TENEBRIONOIDEA; INSECTA; TAXONOMIA; ESPECIES NUEVAS; REGISTRO; CHILE; OXICOPIS CERDAI